THE ANALYSIS OF TEACHER TALK ON ENGLISH FOR YOUNG LEARNER CLASS - Salam, Annisa Yuliana; Taufik, Muh.; N, Jusmaniar. (VARIABLE RESEARCH JOURNAL, 2025)
This study aims to analyze the form and characteristics of teacher talk and its influence on students' understanding and speaking skills in English learning for early childhood at Bahana Islamic School Kindergarten Makassar. A qualitative approach was used with direct observation and audio recording methods to identify teacher communication patterns during the teaching and learning process. The results showed that teachers used various communication strategies such as the use of simple language, repetition, praise, and visual aids to improve student understanding. In addition, it was found that the dominant interaction pattern was Initiation-Response-Feedback (IRF), where the teacher initiates communication, students respond, and the teacher provides feedback. Strategies such as code-switching between English and Indonesian were also used strategically to ensure student understanding. The effective use of teacher talk has been shown to create a positive learning atmosphere and support children's language development, encourage active participation, and build confidence in using English. This study concludes that teacher talk plays an important role in forming an interactive